Long-term results of bipolar hemarthroscopic treatment of elderly and senile women with multiple fragment fractures of the proximal femur - Kalchenko, Andrii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Treatment of elderly and senile patients with fractures of the proximal femur remains an relevant problem in clinical medicine. Joint replacement in such patients is an alternative to osteosynthesis. Objective: to study the long-term results of treatment of elderly and senile patients with fragment fractures proximal femur by the method of bipolar hemiarthroplasty. Methods: the results of treatment of 20 patients (mean age (79.2 ± 9.1) years) with proximal femur fractures evaluated by cement bipolar hemiarthroplasty with augmentation and fixation with wires were evaluated. In 60 % of the patients there were fractures of type 31A2 according to AO/ASIF classification, in 25 % — 31A3. All have a concomitant pathology with the prevalence cardiovascular system deseases. The pain syndrome, the static-dynamic activity of the patients, the deformation and the amplitude of the movements of the operated limb were evaluated using the Harris score. Results: excellent and good results were obtained in 95 % of patients, unsatisfactory — in 5 %. The evaluation o f t he f unctional s tate a ccording t o the Harris s core i ncreased from (64.9 ± 13.4) scores on the 12th day to (86.3 ± 6.9) and (89.5 ± 4.8) scores at 2 months and 3–5 years respectively. Conclusions: the results of treatment of elderly and senile patients with fragment fractures of proximal femur using the method of bipolar hemiarthroplasty testify to its effectiveness. The use of this method allows to improve the quality of life in patients after surgery due to the early function of the hip joint and the damaged lower limb. Preservation of bone fragments and their wire fixation during joint replacement of lateral fractures of the femur provides stability of the implant, helps minimize its «subsidence» in the femoral canal.